Pengembangan Multimedia Interaktif Pada Materi Data Flow Diagram Untuk Mahasiswa Teknik Informatika - Costa, Cecilia Da; Kuswandi, Dedi; Wedi, Agus (JKTP: Jurnal Kajian Teknologi Pendidikan, 2023)
Students have difficulty learning data flow diagram material because of the lack of references and constraints in accessing other reference sources. In addition, students also have difficulty understanding the notations and symbols used in making DFDs. Therefore interactive multimedia aims to produce computer-based learning products, which can be used by students as a source of learning media in making data flow diagrams at the Instituto Superior Cristal. The resulting interactive multimedia product is in the form of an .exe file. so that it is easy for students to use. This development research uses the Lee & Owens 2004 model. This model has five stages, namely, Analysis, Design, Development, Implementation, and Evaluation. The validity test of interactive multimedia products was carried out by media experts and material experts, and gave comments that multimedia was feasible to use. Practicality and attractiveness tests were carried out by informatics students at the Instituto Superior Cristal and gave positive responses in using interactive multimedia in small group and large group trials. Thus the interactive multimedia product on data flow diagram material is declared valid, practical and interesting to be used by students in the learning process at the Instituto Superior Cristal.AbstrakMahasiswa kesulitan dalam pembelajaran Materi data flow diagram karena minimnya referensi dan terkendala dalam mengakses sumber  referensi lain . Oleh karena itu  Multimedia interaktif bertujuan untuk menghasilkan produk pembelajaran, berbasis komputer yang dapat digunakan oleh mahasiswa sebagai salah satu sumber media pembelajaran  dalam pembuatan data flow diagram di Instituto Superior Cristal. Produk multimedia interaktif yang dihasilkan  berupa file .exe. sehingga mudah digunakan oleh mahasiswa. Penelitian pengembangan ini menggunakan model Lee & owens 2004. Pada model tersebut memiliki lima tahapan yaitu, Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Uji kelayakan produk multimedia interaktif dilakukan oleh ahli media dan ahli materi, dan memberikan tanggapan bahwa multimedia layak untuk digunakan. Uji kepraktisan dan kemenarikan  dilakukan oleh mahasiswa informatika Instituto Superior Cristal dan memberikan respon yang positif dalam  menggunakan multimedia interaktif. Dengan demikian  produk multimedia interaktif pada materi data flow diagram  dapat digunakan oleh mahasiswa dalam proses pembelajaran di Instituto Superior Cristal.